2014
DOI: 10.1111/fcp.12061
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the antiepileptic, ethosuximide impacts on neurogenesis of rat forebrain stem cells

Abstract: Specific GABAergic interneurons in the hilus are lost in animal models with temporal-lobe epilepsy (TLE). Some preclinical evidence has indicated that GABAergic cells may provide relief from seizures in these models. This study was aimed to examine the ability of ethosuximide, an anticonvulsant drug, to promote neurogenesis in 3-day-old rat forebrain cortex stem cells. Most of the cells were found to be nestin-positive undifferentiated neural stem cells prior to their exposure to ethosuximide. It was noted tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…In our study, LEV was administered chronically for 10 days at a dose of 10 mg/kg starting 72 h after SE induction. The LEV dose was selected based on our previous studies [13,27], but we also took into account the relatively low dose of C11 (20 mg/kg). It was reasonable to choose similar doses for both the aforementioned anticonvulsants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, LEV was administered chronically for 10 days at a dose of 10 mg/kg starting 72 h after SE induction. The LEV dose was selected based on our previous studies [13,27], but we also took into account the relatively low dose of C11 (20 mg/kg). It was reasonable to choose similar doses for both the aforementioned anticonvulsants.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by Sakai et al [12], indicating that prenatal VPA exposure in mice impairs neuronal migration in the adult dentate gyrus through the decreased expression of CXC motif chemokine receptor 4 (Cxcr4) in NPCs and, consequently, increases seizure susceptibility, whereas voluntary running overcomes these adverse effects. Sondosi and coworkers [13] showed that ethosuximide (ETS) has the ability to induce neuronal differentiation into GABAergic neurons that may explain one of the mechanisms of antiepileptic effects of ETS in rat forebrain stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although acute seizures lead to an increase of proliferation of newborn cells, hippocampal neurogenesis is reduced at chronic stages of epilepsy [27]. Moreover, treatment with antiepileptic drugs may also have various impact on neurogenesis [7,8,9,10]. …”
Section: Discussionmentioning
confidence: 99%
“…Epileptic seizures should be distinguished among the most common stimuli, as they change not only the extent, but also the pattern of neurogenesis. In addition to seizures, antiepileptic drugs also have a significant impact on neurogenesis [7,8,9,10,11]. One of the well-known first-line antiepileptic drugs is valproic acid (VPA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation